2011
DOI: 10.1016/j.jelechem.2010.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous real-time measurement of EEG/EMG and l-glutamate in mice: A biosensor study of neuronal activity during sleep

Abstract: We report on electroencephalograph (EEG) and electromyograph (EMG) measurements concurrently with real-time changes in L-glutamate concentration. These data reveal a link between sleep state and extracellular neurotransmitter changes in a freely-moving (tethered) mouse. This study reveals, for the first time in mice, that the extracellular L-glutamate concentration in the pre-frontal cortex (PFC) increases during periods of extended wakefulness, decreases during extended sleep episodes and spikes during period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 42 publications
8
55
0
Order By: Relevance
“…1A) revealed a significant decrease in basal currents (Pre ϭ 2.60 Ϯ 0.24 nA vs. Post ϭ 0.51 Ϯ 0.06 nA; P Ͻ 0.01) coupled with an approximately twofold decrease in their sensitivity to both Glu (1.54 Ϯ 0.08 nA/10 M) and ascorbate (0.35 Ϯ 0.04 nA/250 M). This decrease in sensitivity is consistent with other studies using sensors of similar design (Behrend et al 2009;Naylor et al 2011) and may be due in part to fouling of the active surface (Kulagina et al 1999) or perturbation of the enzyme layer during sensor removal from the brain. Despite decreases in sensitivity to both substances, the Glu-ascorbate Fig.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…1A) revealed a significant decrease in basal currents (Pre ϭ 2.60 Ϯ 0.24 nA vs. Post ϭ 0.51 Ϯ 0.06 nA; P Ͻ 0.01) coupled with an approximately twofold decrease in their sensitivity to both Glu (1.54 Ϯ 0.08 nA/10 M) and ascorbate (0.35 Ϯ 0.04 nA/250 M). This decrease in sensitivity is consistent with other studies using sensors of similar design (Behrend et al 2009;Naylor et al 2011) and may be due in part to fouling of the active surface (Kulagina et al 1999) or perturbation of the enzyme layer during sensor removal from the brain. Despite decreases in sensitivity to both substances, the Glu-ascorbate Fig.…”
Section: Methodssupporting
confidence: 91%
“…Traditionally, the development of a highly substrate-sensitive and -selective biosensor has been viewed as the most critical factor determining the accuracy of electrochemical measurement of neuroactive substances. With respect to Glu, such sensors were developed in the 1990s (Cooper and Pritchard 1994;Hu et al 1994;Qin et al 2008;Wilson and Gifford 2005) and their use was validated by further in vivo work (Hascup et al 2010;Oldenziel et al 2006), including experiments in awake, behaving animals (Dash et al 2009;John et al 2008;Naylor et al 2011;Uslaner et al 2011). As confirmed in this study, Glu sensors produced by Pinnacle Technology showed in vitro high substrate sensitivity (ϳ0.6 nA/1 M) and reasonably high selectivity against possible interferents, particularly ascorbate and dopamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using separate electrodes to examine glutamate and electrophysiological signals within the same preparation has been a commonly employed method [19][20][21][22] ; however, it is problematic when the separate microelectrodes are not located within the same microenvironment. Several reports delivered external glutamate or drugs that could affect glutamate release into the rat brain and recorded only electrophysiological signal changes [23][24][25][26][27][28] ; however, this method can serve in only a limited capacity for glutamate change is not quantitative.…”
Section: Introductionmentioning
confidence: 99%
“…Current approach is to insert multiple monitoring probes which either limits spatial or time resolution [5]. To overcome these issues, a multifunctional LOT probe was proposed as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%